2021
DOI: 10.2147/jir.s341981
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4-Mediated Immunosuppression in Glioblastoma is Associated with the Infiltration of Macrophages in the Tumor Microenvironment

Abstract: Purpose CTLA4, the immune checkpoint, has been widely reported to contribute to immune evasion in anti-tumor activity. The inhibitors of CTLA4 provide a novel strategy to improve the outcome of peripheral cancer, but their clinical effects are limited in glioblastoma (GBM), thus the comprehensive role of CTLA4 needs to be addressed. Patients and Methods A total of 471 GBM cases were enrolled in this study from 5 cohorts. In our works, the Cancer Genome Atlas (TCGA) coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…On the one hand, tumor-associated macrophages are closely associated with the tumor malignant progression. It has been reported that the infiltration of macrophages might result in CTLA4-mediated immune suppression and lead to poor prognosis in glioblastoma patients (Guan et al, 2021). Asgharzade et al reported the infiltration of macrophages in metastatic NB (Asgharzadeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, tumor-associated macrophages are closely associated with the tumor malignant progression. It has been reported that the infiltration of macrophages might result in CTLA4-mediated immune suppression and lead to poor prognosis in glioblastoma patients (Guan et al, 2021). Asgharzade et al reported the infiltration of macrophages in metastatic NB (Asgharzadeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells and macrophages, TPM4 expression showed an increasing trend as the WHO grade increased, suggesting that TPM4 abnormality was mainly attributed to tumor progression and tumor-associated macrophage (TAM) infiltration, which was further confirmed in the subsequent pseudotime trajectory analysis. As a critical cell subpopulation of TME, TAMs have been concluded to play a vital role in promoting the genesis and progression of glioma [ 31 , 32 ]. Particularly, M2 polarization of macrophages is significantly associated with aggressive progression across different malignancies, especially with immune escape of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the expression of the CD95 (Fas) ligand by GBM cells can also attenuate immune attack through the induction of CD95-Dependent apoptosis in infiltrating lymphocytes[ 69 ]. In turn, CTLA-4 is also an important ICs due to its capacity to compete with CD28 for binding to costimulatory molecules (CD80 and CD86) on antigen-presenting cells, thereby precluding the activation of T cells[ 67 , 68 , 70 , 71 ]. Lastly, indoleamine 2,3-dioxygenase 1 (IDO) and Lectin-like transcript-1 (LLT-1), are known to increase intratumoral Treg and myeloid-derived suppressor cells, and to repress NK cell activity, respectively[ 72 , 73 ].…”
Section: Pivotal Role Of the Tumor Microenvironmentmentioning
confidence: 99%